Designing a Test to Measure the Speed of Field Decision-Making Using Illustrated Playing Situations Among Football Players - Hameed, Saher (Pubmedia Jurnal Pendidikan Olahraga, 2025)
This research aims to design a scientific test to measure the on-field decision-making speed of youth football players using real, illustrated playing situations (photos and video clips). The research adopted a descriptive-experimental approach, and (30) youth players from Anbar Governorate, aged between 18 and 21, with at least three years of coaching experience, participated in it. A test was designed that included (12) illustrated playing situations taken from official matches, depicting offensive and defensive situations requiring immediate decisions. These were displayed on a large screen within a structured testing environment. Response times for each situation were determined in seconds, and decisions were recorded by having players select one of several options associated with each situation. The validity of the test was verified by presenting it to a group of experts, and reliability was calculated using a test-retest. The results showed a statistically significant correlation coefficient. The results showed that players in offensive positions were faster in making decisions than their defensive colleagues, reflecting differences in mental processing speed depending on the tactical tasks. The study concludes that the video test can be used as an objective and practical tool to assess players' field intelligence. It can also be used in player selection and the design of cognitive training programs aimed at improving decision-making speed under pressure. The study recommends developing interactive digital versions of the test and using them to assess the development of mental performance during various training phases.